1999
DOI: 10.1007/s11661-999-1003-y
|View full text |Cite
|
Sign up to set email alerts
|

Atom probe and transmission electron microscopy investigations of heavily drawn pearlitic steel wire

Abstract: Transmission electron microscopy (TEM) and atom probe field ion microscopy (APFIM) observations of pearlitic steel wire show that drawing to a true strain of 4.22 causes fragmentation of cementite lamellae into nanoscale grains. The drawing strain amorphizes some portions of the cementite lamellae in regions where the interlamellar spacing is very small, but most of the cementite lamellae are polycrystalline with nanoscale grains. The carbon concentration in the ferrite is inhomogeneous and varies from 0.2 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(65 citation statements)
references
References 21 publications
3
61
1
Order By: Relevance
“…Upon large reductions, areas containing no cementite particles appeared in the previously observed pearlite structure [22]. Experimental confirmation of nonuniform distribution of carbon atoms in ferrite is reported in [17,18], where the authors considered the use of atomic-probe analysis that allows detection of the spatial distribution of carbon atoms. In the patented and subsequently drawing-deformed (ε = 4.22) steel with 0.82% C, the average carbon concentration in ferrite was shown to be noticeably higher than the equilibrium value and equal tõ 2 at.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Upon large reductions, areas containing no cementite particles appeared in the previously observed pearlite structure [22]. Experimental confirmation of nonuniform distribution of carbon atoms in ferrite is reported in [17,18], where the authors considered the use of atomic-probe analysis that allows detection of the spatial distribution of carbon atoms. In the patented and subsequently drawing-deformed (ε = 4.22) steel with 0.82% C, the average carbon concentration in ferrite was shown to be noticeably higher than the equilibrium value and equal tõ 2 at.…”
Section: Resultsmentioning
confidence: 90%
“…In the course of plastic deformation of patented wire, complex physical processes take place in both ferrite and cementite components of pearlite. There are papers that report the formation of the cellular substructure [2][3][4][5][6][7][8][9][10][11][12][13] in ferrite plates; changes in the chemical composition of cementite upon deformation [14][15][16][17][18][19][20][21][22] and, consequently, in its physical-mechanical properties; the formation of metastable ferric carbide with a higher carbon content [15,16,23,24]; and a partial dissociation of cementite at large deformations. All these processes differently affect the ability of a patented wire to be deformed and lose plasticity, i.e., the phenomenon of "overhardening.…”
mentioning
confidence: 99%
“…The cementite dissoboundaries, or at the edge of the larger grains. Therefore, it lution was also observed in heavily drawn pearlite steel is expected that the shear band is a necessary precursor wires, [27,28,29] and there exist different explanations about the for nanocrystalline formation. However, in recent study on mechanism of cementite dissolution during severe plastic cryomilling Zn powder, the formation of a large number of deformation.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent study on mechanism of cementite dissolution during severe plastic cryomilling Zn powder, the formation of a large number of deformation. [25][26][27][28][29] small grains (2 to 6 nm) in the very early cryomilling stage…”
Section: Introductionmentioning
confidence: 99%
“…and (c) nonstoichiometric composition of cementite resulting from an introduction of excessive imperfections in cementite by intense plastic straining. [28] The recent investigation [8] REFERENCES demonstrated that enhanced spheroidization behavior of carbon atoms are able to diffuse further away from the…”
Section: Discussionmentioning
confidence: 99%